(untitled) (Archive of Conferences, 2021)
Amir Temur’s great contribution to history is that he improves the procedures, legal framework, spiritual and educational aspects of the domestic and foreign policy of the state system of governance in the new historical conditions. In this regard, our first President IA Karimov said: Amir Temur is our glory, our pride. The symbol of Amir Temur’s genius of our people is a symbol of our spiritual power. To understand the personality of Amir Temur, to know the history means to understand ourselves. To honor Amir Temur is to strengthen our confidence in our great future, based on our cultural strength and deep-rooted roots in history. The state of Amir Temur developed science, spirituality, enlightenment and industry at an unprecedented rate, and in science it was rightly interpreted as the second period of the Renaissance